Determination of the preferred sugar in the diet of Lutzomyia evansi (Nuñeztovar) (Diptera: Psychodidae) - BASTIDAS-P., GILBERTO; OVIEDO, MILAGROS; VIVENES-J., ALEJANDRA; GONZÁLEZ, ADALBERTO (Revista Colombiana de Entomología, 2004)
Sugars have been shown to play an important role in the biology and relationship between the host and parasitic Leishmania. Under experimental conditions, the preferred sugars in the diet of Lutzomyia euansi, alternate vector of Leishmania chagasi, were determined. After the depletion of their natural sugars, females from the wild and females from a colony of L. euansi were periodically offered, over a period of 72 hours. fructose, saccharose, melezitose, glucose, galactose, and maltose, identified by different vegetable colorings; the ingested sugar was determined by its color under a binocular magnifying glass. The results were compared with those from a colony of L. longipalpis. Of 618 wild L. euansi studied. fructose was detected in 340 females (55%), regardless of the color used, followed by melezitose ( 18,6%) and saccharose ( 15,5%). Similar results were obtained from 199 females from the colony. In contrast. L. longipalpis preferred saccharose (34%), followed by glucose (29%) and fructose (24%). The anthrone test detected the presence of fructose in 55,5% of the sample of females from the wild. These discoveries are relevant to the biology of the species and could be significant in the establishment and pattern of parasite development inside the insect vector.